Buying Rural Land in Texas - Gilliland, Charles E. (Charles Edward) (Book collections on Project MUSE., 2012)
Whether the prospective buyer is a farmer or rancher looking to expand operations, a sportsman seeking to preserve habitat for wildlife, or a nature enthusiast trying to conserve native flora and fauna, acquiring rural land can be a rollercoaster of exciting and stressful experiences. In Buying Rural Land in Texas: Taking the Right Risk, Charles E. Gilliland demonstrates that buyers can and should arm themselves with knowledge-of the land-buying process, of the potential problems involved, and of the resources available to them-to ensure a successful and satisfying outcome. In this practical guide, Gilliland outlines four phases of buying rural land: identifying what you want, in terms of both land and property rights; locating a suitable property; valuing the property; and completing the transaction. He then covers everything the potential landowner should know while progressing through these steps: how to identify and manage risk, plan an "exit strategy," interpret present and future land prices, find the "perfect spot," evaluate the property's physical attributes, gauge economic trends, understand legal rights and limitations, protect natural resources, and, finally, close the deal. Incorporating real life examples from a career spent in land sales, Gilliland takes readers step-by-step through the process, also providing checklists, maps, professional tips, and information about how to tap additional sources of information and advice. With the knowledge gained from Buying Rural Land in Texas, new landowners will find themselves not at the end of a journey but at the beginning, as they learn to manage their land and to deliver it intact to future generations